Multimorbidity and health-related quality of life in Koreans aged 50 or older using KNHANES 2013–2014 - Bomi Park; Minsu Ock; Hye Ah Lee; Seonhwa Lee; Hyejin Han; Min-Woo Jo; Hyesook Park (Health and Quality of Life Outcomes, 2018)
Abstract Background Multimorbidity negatively affects health outcomes and impairs health-related quality of life (HRQoL). We assessed the prevalence of multimorbidity in Koreans aged 50 and older, taking into consideration their socioeconomic status, and estimated the loss in HRQoL due to multimorbidity. Methods This study is based on an analysis of data for adults aged 50 and older derived from the cross-sectional nationally representative Korean National Health and Nutrition Examination Survey conducted in 2013–14. The five most prevalent chronic diseases and disease dyads were identified. The impact of the degree of multimorbidity, sex, and socioeconomic status on the European Quality of Life 5 Dimension (EQ-5D) index score were analyzed. Marital status, educational attainment, household income, basic livelihood security benefit, and occupation were considered as socioeconomic factors. Results The analysis included 5996 adults aged 50 years and older with males comprising 46.6%. Two or more chronic diseases were present in 26.8% of the participants aged 50 and older and 37.9% of the participants aged 65 and older. The most prevalent dyadic combination was hypertension and dyslipidemia in the 50 and older group, and hypertension and osteoarthritis in the 65 and older age group. Hypertension dominated the multimorbidity combinations (four of the five most prevalent multimorbidity dyads), while a few conditions such as osteoarthritis had a relatively large influence on quality of life. In addition to the degree of multimorbidity, female and lower socioeconomic status were associated with significantly lower EQ-5D index scores. Conclusions Integrated, holistic healthcare based on a patient-oriented perspective for earlier, more effective intervention, targeting multimorbidity is warranted. Special consideration should be given to patients with low socioeconomic status.